Single-cell RNA-seq identification of four differentially expressed survival-related genes by a TARGET: Osteosarcoma database analysis. Issue 11 (June 2022) - Feleke, Mesalie; Feng, Wenyu; Rothzerg, Emel; Song, Dezhi; Wei, Qingjun; Kõks, Sulev; Wood, David; Liu, Yun; Xu, Jiake
Osteosarcoma (OS) differentially expressed genes (DEGs) have been predicted using the data portal of the Therapeutically Applicable Research to Generate Effective Treatments (TARGET). In this study, we sought to identify cell types that specially express key DEGs ( MUC1, COL13A1, JAG2, and KAZALD1 ) in each of the nine identified cell populations derived from tissues of OS tumors with single-cell RNA-sequencing data. Gene expression levels were pairwise compared between cell clusters and a p value < 0.05 was considered differentially expressed. It was revealed that MUC1 is expressed at high levels in osteoblastic OS cells followed by carcinoma-associated fibroblasts (CAFs) and plasmocytes, respectively. COL13A1 is highly expressed in osteoblastic OS cells, CAFs, and endothelial cells (ECs), respectively. The KAZALD1 gene is expressed in CAFs and osteoblastic OS cells at high levels, but at very low levels in plasmocytes, osteoclasts, NK/T, myeloid cells 1, myeloid cells 2, ECs, and B cells. JAG2 is expressed at significantly high levels in ECs and osteoblastic OS cells, and at relatively lower levels in all other cell types. Interestingly, LSAMP, as an established gene in the development of OS shows high expression in osteoblastic OS cells and CAFs but low in other cells such as osteoclasts. Our findings here highlight the heterogeneity of OS cells and cell-type-dependent DEGs which have potential as therapeutic targets in OS.